Leaf epidermal character variation and evolution in Gaultherieae (Ericaceae). (12th June 2015) - Wang, Yin‐Huan; Lu, Lu; Fritsch, Peter W.; Wang, Hong; Wang, Yue‐Hua; Li, De‐Zhu
<x xml:space="preserve">Abstract</x> The taxonomic value and evolutionary significance of 30 leaf epidermal characters from 238 samples representing 127 species of all seven genera in the tribe Gaultherieae (Ericaceae) and two outgroup genera were investigated by scanning electron microscopy. The character states were coded and optimized onto a maximum‐likelihood tree based on previous molecular data with Fitch parsimony and hierarchical Bayesian analysis to trace the evolution of character states throughout all internodes in the phylogenetic tree for Gaultherieae. Leaf epidermal characters were found to be largely consistent within species, but highly variable at interspecific and higher taxonomic levels. The most recent common ancestral states of 15 characters diagnosed various lineages recovered from prior studies, some with no prior morphological support. Relatively high frequencies of state change occur in the eastern Asian clade Gaultheria series Gymnobotrys + Diplycosia, the American clade G. subsection Dasyphyta p.p., the core East Asian clade and the Australia/New Zealand clade. The characters with the highest frequencies of state change are the outer stomatal ledge ornamentation type, the stomatal apparatus level, stomatal density and area, and the type of abaxial trichomes. These character state change patterns may provide insight into the ecological adaptions of Gaultherieae during their evolutionary history. © 2015 The Linnean Society of London, Botanical Journal of the Linnean Society, 2015, 178, 686–710.